Ultrasound-guided selective supraclavicular nerve block combined with modified clavipectoral fascial plane block for midshaft clavicule fracture surgery: a case report - Fei Jiang; Na-na Li; Yong Yang; Di Liu (BMC Anesthesiology)
Abstract Background Conventional anesthesia for clavicular fracture surgery poses significant challenges. General anesthesia risks pulmonary complications, while traditional nerve blocks may cause diaphragmatic paralysis or motor impairment. Ultrasound-guided techniques improve precision, but standalone superficial cervical plexus or interscalene brachial plexus blocks often fail to fully anesthetize the deep clavicular region, especially in polytrauma patients. An optimized combined approach could provide effective analgesia while preserving respiratory and motor function. Case presentation A 65-year-old male patient with a comminuted fracture of the middle right clavicle and multiple injuries underwent surgery with an ultrasound-guided selective supraclavicular nerve block (SSNB) combined with a modified clavipectoral fascial plane block (MCPB), referred to here as SSCPB. The supraclavicular nerve and clavipectoral fascia were precisely located using ultrasound, and 0.4% ropivacaine was administered, supplemented with dexmedetomidine and sufentanil. The patient maintained stable intraoperative vitals with no pain responses and preserved diaphragmatic/limb function. Postoperatively, analgesia was excellent (VAS 0–2 at rest, 3 on movement) without neurological compromise. Conclusion The SSCPB technique achieves optimal anesthesia for mid-clavicular fracture surgery by combining SSNB with MCPB. This approach effectively prevents diaphragmatic paralysis and upper limb dysfunction, making it particularly suitable for patients with concomitant cardiopulmonary injuries or comminuted fractures. Characterized by its simplicity in operation and high safety profile (avoiding general anesthesia-related risks), SSCPB reduces opioid dependence and promotes postoperative recovery. However, more extensive clinical research is required to establish its long-term safety and efficacy profile, particularly in complicated acromioclavicular joint dislocations where adjunctive sedation or suprascapular nerve blocks might be indicated.